2011
DOI: 10.1007/s00467-011-1797-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal amyloidosis in children

Abstract: Renal amyloidosis is a detrimental disease caused by the deposition of amyloid fibrils. A child with renal amyloidosis may present with proteinuria or nephrotic syndrome. Chronic renal failure may follow. Amyloid fibrils may deposit in other organs as well. The diagnosis is through the typical appearance on histopathology. Although chronic infections and chronic inflammatory diseases used to be the causes of secondary amyloidosis in children, the most frequent cause is now autoinflammatory diseases. Among this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 97 publications
2
65
0
2
Order By: Relevance
“…These entire laboratory parameters usually return to normal in the attack-free periods [7]. However, it has been reported that subclinical inflammation may continue during the attack-free periods in some patients and may lead to the development of amyloidosis [8, 9] that maybe complicated by end-stage renal disease [10]. …”
Section: Introductionmentioning
confidence: 99%
“…These entire laboratory parameters usually return to normal in the attack-free periods [7]. However, it has been reported that subclinical inflammation may continue during the attack-free periods in some patients and may lead to the development of amyloidosis [8, 9] that maybe complicated by end-stage renal disease [10]. …”
Section: Introductionmentioning
confidence: 99%
“…This type of subclinical inflammation has a chronic course and leads to the development of the most mortal complication named amyloidosis. And amyloidosis can be controlled with the inhibition of this inflammation [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Vasculitis is a newly defined entity in FMF [4,9,10]. Cochlear involvement has been shown to be a component of the diseases in which vasculitis is predominant in the physiopathological mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Since vasculitic diseases and amyloidosis are seen frequently during the course of FMF and the disease involves many organs as kidneys, central nervous system, heart, respiratory and gastrointestinal tracts by amyloidosis or vasculitis, cochleovestibular involvement related to the course of the disease is probable [4,5]. To our knowledge, otological involvement in FMF has not been studied until now.…”
mentioning
confidence: 98%